Investigation into fault detection and diagnosis techniques - Patel, B (Department of Electrical Engineering, 2026)
The early detection and diagnosis of faults in systems is one of the most important tasks assigned to the computers supervising these systems. The early indication of abrupt or incipient failures can assist in avoiding major system breakdowns and catastrophes, which could otherwise result in substantial material damage and even human fatalities. Furthermore, these systems should be designed with the properties that any good fault detection and diagnosis scheme should incorporate. These properties include isolability, sensitivity, robustness, reliability, maintainability, survivability and the ability to be reconfigurable. From the beginning of process control, most practical systems have contained some form of fault detection and diagnosis. In the majority of these systems, the detection and diagnostic function is rather simple, being based on straight limit checking. The development of computational equipment has set the scene for the general application of more sophisticated and powerful methods.